British Association for Psychopharmacology consensus statement on evidence-based treatment of insomnia, parasomnias and circadian rhythm disorders: An update. (August 2019) - Wilson, Sue; Anderson, Kirstie; Baldwin, David; Dijk, Derk-Jan; Espie, Audrey; Espie, Colin; Gringras, Paul; Krystal, Andrew; Nutt, David; Selsick, Hugh; Sharpley, Ann
This British Association for Psychopharmacology guideline replaces the original version published in 2010, and contains updated information and recommendations. A consensus meeting was held in London in October 2017 attended by recognised experts and advocates in the field. They were asked to provide a review of the literature and identification of the standard of evidence in their area, with an emphasis on meta-analyses, systematic reviews and randomised controlled trials where available, plus updates on current clinical practice. Each presentation was followed by discussion, aiming to reach consensus where the evidence and/or clinical experience was considered adequate, or otherwise to flag the area as a direction for future research. A draft of the proceedings was circulated to all speakers for comments, which were incorporated into the final statement.